2011
DOI: 10.1186/1753-2000-5-18
|View full text |Cite
|
Sign up to set email alerts
|

Parent experiences questionnaire for outpatient child and adolescent mental health services (PEQ-CAMHS Outpatients): reliability and validity following a national survey

Abstract: AbstactBackgroundDevelopment and evaluation of the PEQ-CAMHS Outpatients, a parent completed questionnaire to measure experiences of outpatient child and adolescent mental health services (CAMHS) in Norway.MethodsLiterature review, parent interviews, pre-testing and a national survey of 17,080 parents of children who received care at one of the 86 outpatient CAMHS in Norway in 2006. Telephone interviews were conducted with a random sample of non-respondents. Levels of missing data, factor structure, internal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 26 publications
4
40
0
Order By: Relevance
“…The findings from a Norwegian follow-up study involving a similar inpatient population showed that postal respondents and non-respondents had almost the same patient-reported experience scores 27. This is in line with the results of other Norwegian user-experiences studies,28 29 indicating that the response rate exerts only minor effects.…”
Section: Discussionsupporting
confidence: 91%
“…The findings from a Norwegian follow-up study involving a similar inpatient population showed that postal respondents and non-respondents had almost the same patient-reported experience scores 27. This is in line with the results of other Norwegian user-experiences studies,28 29 indicating that the response rate exerts only minor effects.…”
Section: Discussionsupporting
confidence: 91%
“…First, the design of this study did not assess test-retest reliability. For now, we must rely on satisfactory findings from the PEPC questionnaire and modifications [22, 27]. Additionally, the focus group could have included a higher number of family members than three to secure a broader covering of themes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, included in the PEPC questionnaire was several other single questions of possible interest in the family experiences questionnaire developmental process: nine questions about health care delivery, overall satisfaction with care and how the parents were treated, the extent to which parent expectations were met, information about medication, extent of poor treatment, and extent of any problems with the staff. Good validity, internal consistency and test-retest reliability have been reported [22, 27]. …”
Section: Methodsmentioning
confidence: 99%
“…The conceptual approach was further developed and refined as part of the project, but the study did not follow our standard development and validation process. [12][13][14][15] An internal reference group was used instead of an external group, and we only conducted cognitive interviews with patients, not indepth interviews. The inclusion of the PRIH-I within an existing patient-experience questionnaire gave rise to space restrictions.…”
Section: Limitationsmentioning
confidence: 99%
“…Our standard development and validation process was the starting point for this project, [12][13][14][15] including multiple activities to ensure content validity in the development phase, and a set of psychometric tests in the quantitative phase to assess instrument quality. Adjustments had to be made because of time restrictions and the measurement construct, the latter in particular resulting in substantial changes.…”
Section: Introductionmentioning
confidence: 99%